OPTIMALISASI PELAKSANAAN REKRUTMEN BINTARA POLRI DI PROVINSI KALIMANTAN TENGAH: OPTIMIZATION OF RECRUITMENT OF POLICE PETTY OFFICERS IN CENTRAL KALIMANTAN PROVINCE - Noviandhi Wahyu Bintoro; Muhamad Yusuf; Nova Riyanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This study aims to analyze the inhibiting factors of the selection mechanism and the implementation of recruitment that has been carried out at the Central Kalimantan Police in order to form a professional NCO candidate. The method in this research is a qualitative descriptive type which aims to describe the implementation of the recruitment of the National Police NCO in the Context of Formation of qualified, clean, transparent, accountable and humanist National Police Human Resources in order to create professional, modern and reliable NCO personnel at the Central Kalimantan Police. The data of this research were obtained from direct observation, interviews, and collecting documents. The informants in this study were: Head of HR Department of the Central Kalimantan Police, Head of the Central Kalimantan Regional Police's HR Bureau, Head of the Central Kalimantan Regional Police's HR Bureau, Head of the Central Kalimantan Police's HR Bureau of Diapers, Paur Central Kalimantan Regional Police's HR Subdivision Paur, and the participants who took part in the NCO selection. The results show that the mechanism that has been implemented so far in the recruitment of the Central Kalimantan Police NCO has gone through the stages set by the Central Committee/Police Headquarters but in its implementation it is still not optimal due to several obstacles in each series of selection stages.